Mark Morris' I'allegro, il pensoroso ed il moderato, A Celebration Book review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2001)
PALABRAS CLAVE: Mark Morris, L'Allegro, il penseroso ed il moderato.
Mark Morris' I'allegro, il pensoroso ed il moderato, A Celebration. Edited by Jeffrey Escoffier and Matthew Lore. Robert Hale, 2001.